Influence of Opening and Boundary Conditions on the Behavior of Concrete Hollow Block Walls: Experimental Results - Kabiru A. Musa; Badorul Hisham Abu Bakar; Ufuoma Joseph Udi (Journal of Engineering and Technological Sciences, 2023)
The assembled pattern of concrete hollow building blocks contributes to the wall structure’s durability. This paper presents experimental research on the behavior of concrete hollow block walls. The experimental work included testing four concrete hollow block wall panels with different opening sizes. Constant vertical axial load was applied on top of the wall panels until failure, characterized by boundary conditions. The results showed that the presence of openings reduced the strength of the wall panels; it was possible to observe these differences since the opening area was between 20 and 40% of the gross wall panel area. It was also observed that while the opening percentage had a significant impact on the strength of the wall, the boundary conditions had a less substantial impact on the overall wall response. A high localized concentration of stress was observed at the top corners of the wall panels and a high stress concentration was also observed along the vertical sides of the openings. Variation in the number and the shape of the openings often changed the failure mechanism in the wall panels, even when the percentage area of the opening remained constant. The wall panels A1-B2 reached peak stress levels at 0.019 MPa, 0.036 MPa, 0.056 MPa, and 0.030 MPa. The equivalent peak strains were 0.018, 0.011, 0.012, and 0.010 respectively. This research established significant data and is expected to help in the design and analysis of axially loaded unreinforced masonry walls with openings.